Gastric lavage to reduce feed intolerance among vigorous neonates >34 weeks born through meconium stained liquor: A comparative study - Manoj Kumar Gupta; Dhirendra Prasad Yadav; Mohammad Ashfaque Ansari; Mukendra Sah (Asian Journal of Medical Sciences, 2023)
Background: Feed intolerance during early postnatal period is common in newborns with meconium-stained liquor (MSL). Prophylactic gastric lavage in neonates delivered with MSL and its recommendation by some pediatric textbooks, despite negligible scientific evidence and evidence-based recommendations. Aims and Objectives: This study was designed with the objective of determining if gastric lavage in all babies with MSL led to the development of less feed intolerance as compared to those who were not subject to the procedure. Materials and Methods: The present study was a randomized control trial, conducted at National Medical College and Teaching Hospital, Birgunj, from December 01, 2021, to November 30, 2022. The study populations were 280 vigorous neonates with ≥34 weeks of gestation and ≥1800 g delivered with MSL. Among them, 140 neonates were kept in the lavage and non-lavage group. Data were analyzed using the Chi-square test, odds ratio, and level of significance at P<0.05. Results: Thirty-two (22.85%) and 54 (38.57%) neonate in the lavage and no lavage group developed the first episode of vomiting with a significant P=0.005. No significant difference in the incidence of feed intolerance was found (8.57% vs. 15%, P=0.099). None of the neonates in either group developed any complications during the procedure. Conclusion: Gastric lavage seems to reduce the first episode of vomiting but not overall feed intolerance in vigorous infants born through meconium-stained amniotic fluid. Hence, concluded that gastric lavage should be reserved for treating the rather rare feed intolerance than routine prophylactic in vigorous neonates delivered with MSL.